The impact of PD-L1 polymorphisms on the efficacy of immune checkpoint inhibitors depends on the tumor proportion score: a retrospective study - Keiichiro Suminaga; Takashi Nomizo; Hironori Yoshida; Hiroaki Ozasa (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose This study aims to clarify the relationship between rs2282055, a single-nucleotide polymorphism (SNP) in programmed death-ligand 1 (PD-L1), and TPS. Polcaro et al. (2024) showed that rs822336, a SNP in PD-L1, predicts the effect of immune checkpoint inhibitors (ICIs). However, the study did not show a relationship between rs822336 and the tumor proportion score (TPS), which is currently used as a primary marker. Therefore, we examined this relationship. Method Patients treated with immune checkpoint inhibitor monotherapy for non-small cell lung cancer at Kyoto University Hospital until January 2023, with TPS data and biological specimens available for SNP measurement, were eligible for this study. Genomic DNA was extracted from peripheral blood leukocytes. We used rs2282055, which is in linkage disequilibrium with rs822336, instead of rs822336, because of its distribution in the Asian patient population. We retrospectively extracted data on age, sex, smoking history, driver mutations, TPS, progression-free survival (PFS), and best response to ICI from medical records. Result The rs2282055 T/T genotype was associated with significantly better PFS in the TPS-negative population than in the other genotypes. In contrast, no differences were observed in TPS-positive patients. Conclusion The rs2282055 genotype may help in selecting cases from the TPS-negative patient population that may benefit from ICI therapy.